Genetic polymorphisms associated with steroids metabolism and insulin action in polycystic ovary syndrome - Ramos Cirilo, Priscila Daniele [UNESP]; Rosa, Fabiola Encinas [UNESP]; Moreira Ferraz, Maria Fernanda [UNESP]; Rainho, Claudia Aparecida [UNESP]; Pontes, Anaglória [UNESP]; Rogatto, Silvia Regina [UNESP] (Informa Healthcare, 2012)
Polycystic ovary syndrome (PCOS) is an endocrinopathy associated with infertility, diabetes and cardiovascular events. This study aimed to correlate polymorphisms of genes involved in the biosynthesis and metabolism of steroids and insulin action (CYP17A1, CYP19A1, AR, ESR1, ESR2, INSR, IGF2 and PAI1) with clinical and biochemical parameters of PCOS. DNA was extracted from peripheral blood samples obtained from 117 PCOS and 105 healthy women. The PAI1 insertion/deletion (-675 ins/delG) polymorphism (rs1799768) was genotyped by PCR-SSCP. CYP19A1 [TTTA](n), AR [CAG](n), ESR1 [TA](n), and ESR2 [CA](n) genes were evaluated by PCR-based GeneScan analysis, while CYP17A1 5'UTR (rs743572), INSR 1058 CT (rs1799817), and IGF2 3'UTR GA (rs680) polymorphisms were evaluated by PCR-RFLP. The results showed a prevalence of PAI1 4G5G+4G4G genotypes in PCOS (p=0.025). Younger PCOS women showed a predominance of CT+TT, GA+AA and 4G5G+4G4G genotypes of INSR, IGF2, and PAI1 (p=0.0499, p=0.0300, p=0.0350, respectively). AR shorter alleles (<= 20 repeats) were significantly associated with higher serum levels of total testosterone (TT, p=0.0086). In conclusion, PAI1 polymorphism seems to be associated with the risk of PCOS development. Younger PCOS women had specific genotypes of INSR, IGF2 and PAI1 genes. AR shorter alleles can be associated with higher serum levels of TT in PCOS patients.
Keywords: Polycystic ovary syndrome; androgen metabolism; androgen receptor; estrogen receptor; insulin resistance; infertility